2000
DOI: 10.1002/(sici)1097-0142(20000315)88:6<1393::aid-cncr17>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Frequency ofBRCA1/BRCA2 mutations in a population-based sample of young breast carcinoma cases

Abstract: BACKGROUND There is a clear and growing need for data regarding BRCA1 and BRCA2 mutation frequencies among breast carcinoma cases not specifically ascertained on the basis of extreme family history profiles. Toward this end, the authors previously reported results with regard to BRCA1 in breast carcinoma patients drawn from a population‐based study. In the current study the authors present new findings concerning BRCA2 mutation frequency in this same population, as well as summary data regarding the combined c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(129 citation statements)
references
References 28 publications
12
113
2
2
Order By: Relevance
“…Indeed, in the present series younger women were likely to have a family history than women in the older group (3% vs 0.3%). Although we do not know the genetic status of our patients, approximately 5% of young patients had a germ-line BRCA1 mutation and a 3% BRCA2 mutation (Malone et al, 2000).…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, in the present series younger women were likely to have a family history than women in the older group (3% vs 0.3%). Although we do not know the genetic status of our patients, approximately 5% of young patients had a germ-line BRCA1 mutation and a 3% BRCA2 mutation (Malone et al, 2000).…”
Section: Discussionmentioning
confidence: 93%
“…31 In the United States, different studies have demonstrated a clear prevalence of BRCA1 mutations. 32,33 In Table 6, the frequencies of BRCA1 and BRCA2 germline mutations among different populations are reported.…”
Section: Discussionmentioning
confidence: 99%
“…Except for genetic predisposition the risk factors for early-onset breast cancer remain to be determined, but may include high body mass index (BMI), Hodgkin's lymphoma, early age at menarche, and early age at first birth (althius and Brogan 2003; Silvera et al 2006;Rodriguez et al 2008;alm El-Din et al 2009). A study conducted within an American population showed that among early-onset breast cancer patients, only ~10% carried deleterious BRCA1 or BRCA2 mutations, and 1% were non-familial (Malone et al 2000). In China, BRCa1 and BRCa2 disease-causing mutations are responsible for ~3% and 0%, respectively, of early-onset breast cancers without a family history of breast or ovarian cancer (Li et al 2007;Ma et al 2008;Chen et al 2009).…”
Section: Tohoku University Medical Pressmentioning
confidence: 99%